Development of Based Learning Multimedia Flipbook on the Subject of Life Organization at SMPIT Al Multazam Kuningan - Ali Nurdin; Wahidin; Anna Fitri Hindriana (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2023)
Learning patterns that only use blackboards, books, worksheets, and PowerPoint slides generally only focus on the teacher while students listen, take notes, and memorize more. This learning pattern can cause boredom and monotonous learning so students are not interested in the learning process. One effort to overcome this problem is to develop appropriate learning media such as flipbook-based learning multimedia. This research was conducted in class VII SMPIT Al Multazam Kuningan to develop flipbook-based learning multimedia. This research was conducted using the R&D (Research and Development) method which refers to the ADDIE model. The percentage of media validation scores by experts is 87% from linguists, 90% from content/material experts, and 89% from media experts. Furthermore, at the trial stage, flipbook-based learning multimedia received an assessment percentage of 89.8% for the material aspect, 87.55% for the language aspect, 88.9% for the media aspect, and 88.75% for the average percentage. These results indicate that flipbook-based learning multimedia is very feasible to be applied in the learning process.